Exploration of Keystroke Dynamics Based Authentication on Fixed-Text and on Free-Text - Rathi, M; Kumar, V. Senthil (International Journal of Computer Sciences and Engineering, 2019)
Computer security is the protection of computing systems and the data that is stored or accessed. It is very important to ensure that the information remains confidential and only those who should access that information can. Username and password alone are insufficient in complex applications. Hence, a strong authentication method such as Biometric authentication method is required to verify one’s identity using the unique biological characteristics of an individual. Existing security approaches can be strengthened by one of the behavioral biometric based technique known as Keystroke Dynamics. The main objective of this paper is to explore particularly on Keystroke Dynamics based Authentication (KDA). This technique can be applied in different domains like intrusion detection, online learning and assessment, e-banking etc., to authenticate the users. This paper presents a review of its applications using fixed-text (static passwords) and free-text (continuous). Comparing these two types of keystroke authentication methods, Free-text kind of authentication process was found to be better as it is not limited with username and password during the log-in session; it is continued until the end of the log-on session.